Detection of blast resistance genes in inbred rice lines using site-specific blast races - Herawati, R.; Bustamam, H.; Fahrurrozi; Alnopri; Ganefianti, D. W.; Marlin; Romeida, A. (International Journal of Agricultural Technology, 2024)
Blast disease attacks by Pricularia oryzae on lowland rice were quite extensive in the Province of Bengkulu, Indonesia. Screening of 19 lines inoculated with four local races (333-BT, 001-BU, 043-RM, and 373-BS) revealed variations in blast disease resistance. There were nine rice lines (G7, G8, G9, G11, G13, G14, G15, G18, and G19) that showed resistance to blast disease with lower severity. There are found the race-sensitive lines with high virulence (333-BT and 373-BS), namely G3, G4, G6, G12, and G17. In addition, races 333-BT and 373-BS tended to show high virulence in sensitive varieties of Kencana Bali. Almost all lines had low levels of severity in low-virulence races (001-BU and 043 RM). Detection of blast-resistant genes using specific primers is found to be detected the existence of the genes Pib, Pii, Pi5, and Pita2. This study found that the G7, G8, G9, G11, G13, G14, G15, G18, and G19 lines are shown to be the potential for further evaluation because they contain the Pii, Pi5, and Pita2 genes, which have multigenic and broad-spectrum blast resistance